PEMERINTAHAN DAN KEKUASAAN NEGARA ISLAM (Kajian Terhadap Pemikiran Ikhwan al-Muslimin) - Candra, Anton Afrizal (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Thought the Ikhwan al-Muslimin movement in priciple assume that islam is comprehensive system (syamil/universal, kamil/perfect,mutakamil/integral) that touches all facets and aspect of life. Ikhwan al-Muslimin rejected the idea of separation between religion and the state or political. All they mention as a thinker whose conception as if it has become an axiom or a large affair that religion should be completely understand, concession was summed up in the phrase that Islam is a faith and religion and state system. So the establishment of the rule of Islam is one of the tenets of Islam and faith or liability is a necessity that can't be bargained.